2005
DOI: 10.1111/j.1365-294x.2005.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Rangewide population genetic structure of the African malaria vector Anopheles funestus

Abstract: Anopheles funestus is a primary vector of malaria in Africa south of the Sahara. We assessed its rangewide population genetic structure based on samples from 11 countries, using 10 physically mapped microsatellite loci, two per autosome arm and the X (N = 548), and 834 bp of the mitochondrial ND5 gene (N = 470). On the basis of microsatellite allele frequencies, we found three subdivisions: eastern (coastal Tanzania, Malawi, Mozambique and Madagascar), western (Burkina Faso, Mali, Nigeria and western Kenya), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
107
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 50 publications
19
107
0
1
Order By: Relevance
“…Previous work predicted that southern Africa was one interbreeding population based on continent-wide analysis (18), but genome-wide genetic diversity analysis using F st comparisons and Bayesian structure analysis has revealed three population clusters in southern Africa. Cluster 1, which includes Zambia and northern Malawi (SLM and NKK), corresponds to greater overexpression of CYP6M7.…”
Section: Multiple Cytochrome P450s Are Driving Pyrethroid Resistance Inmentioning
confidence: 99%
“…Previous work predicted that southern Africa was one interbreeding population based on continent-wide analysis (18), but genome-wide genetic diversity analysis using F st comparisons and Bayesian structure analysis has revealed three population clusters in southern Africa. Cluster 1, which includes Zambia and northern Malawi (SLM and NKK), corresponds to greater overexpression of CYP6M7.…”
Section: Multiple Cytochrome P450s Are Driving Pyrethroid Resistance Inmentioning
confidence: 99%
“…Temu et al [119], showed a similar pattern to the other studies at the country level for five countries in Eastern and Southern Africa: the genetic distance limited the gene flow among populations and promoted genetic differentiation among populations. A comprehensive study using samples across the continent provided important findings [93]. Anopheles funestus was subdivided into three large blocks: West Africa, East Africa and Central Africa [120,121].…”
Section: Molecular Markersmentioning
confidence: 99%
“…funestus genome. They have allowed the analysis of population genetic structure, gene flow and demographic events across Africa [93], from Senegal [40], Cameroon [83,86], Kenya [94] to Madagascar [95], revealing important signatures of local adaptation, dispersion or speciation.…”
Section: Molecular Markersmentioning
confidence: 99%
“…The Bayesian method of Pritchard et al (2000) has the advantage that the uncertainty in the assignment of individuals to populations is easy to characterize. The method has also been of great practical importance, with uses in conservation genetics (Moodley and Harley 2005;Small et al 2006), epidemiology (Leo et al 2005;Michel et al 2005;Nejsum et al 2005;Ochsenreither et al 2006), and studies of population demography (e.g., Rosenberg et al 2002), and is often used as a first step in a genetic association study (Song and Elston 2006;Tsai et al 2006;Yu et al 2006).…”
mentioning
confidence: 99%